2004
DOI: 10.1002/rra.777
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ecological aspects in flood protection strategies: defining an ecological minimum

Abstract: Policy makers are confronted with the question of how to combine sustainable flood protection and floodplain rehabilitation in the best possible way. Both topics deal with spatial planning aspects in a range of scales. This question was the starting point for the development of an evaluation method within the IRMA/SPONGE project Intermeuse, illustrated on the basis of assumed flood protection strategies in the Meuse river basin (the 'sponge' strategy, the 'retention' strategy, and the 'floodplain lowering' or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Increasing anthropogenic activities in these areas however disturb this situation (Ward et al, 1999). Some of these activities target the protection of people and goods from flooding, through bank consolidation and regulation of rivers (Décamps, 1993;Décamps et al, 1988;Geilen et al, 2004). Other human activities concern the use of floodplain resources, such as extraction of gravel, sand or clay, as well as agricultural practices that take advantage of these highly productive lands (Rouquette et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Increasing anthropogenic activities in these areas however disturb this situation (Ward et al, 1999). Some of these activities target the protection of people and goods from flooding, through bank consolidation and regulation of rivers (Décamps, 1993;Décamps et al, 1988;Geilen et al, 2004). Other human activities concern the use of floodplain resources, such as extraction of gravel, sand or clay, as well as agricultural practices that take advantage of these highly productive lands (Rouquette et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Floodplains are often characterized by a mosaic of habitats differing in age, humidity, sediment properties, productivity, and diversity, abundance, composition and succession state of biota (Geilen et al 2004). This habitat mosaic is inhabited by a multiplicity of generalist and specialist species, both terrestrial and aquatic, which often depend on the relative habitat quality and on proximity and functional connectivity of various habitat patches (Romanowski et al 2005;Scholz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vis et al, 2001;Van Asselt et al, 2001;Geilen et al, 2004). It was found that none of the newly developed strategies is superior in all respects, and/or to all parties involved.…”
Section: Evaluation Of Integrated Flood Risk Management Strategiesmentioning
confidence: 93%